Irreversible pulmonary hypertension associated with Troglostrongylus brevior infection in a kitten. (October 2015) - Crisi, Paolo E.; Traversa, Donato; Di Cesare, Angela; Luciani, Alessia; Civitella, Carla; Santori, Domenico; Boari, Andrea
Abstract: A four month-old kitten was referred at the Veterinary Teaching Hospital of Teramo, Italy. Physical examination, echocardiography, thoracic radiography, copromicroscopy and biomolecular assays led to a diagnosis of severe parasitic bronchopneumonia by Troglostrongylus brevior complicated by pulmonary hypertension. A single administration of a spot on solution containing imidacloprid 10%/moxidectin 1% was effective in stopping larval shedding but clinical, radiographic and echocardiographic signs of bronchopneumonia and pulmonary hypertension still persisted after further follow-ups. While cases of pulmonary hypertension are known in infections by Aelurostrongylus abstrusus, this is the first report of irreversible pulmonary hypertension in a kitten with troglostrongylosis. Highlights: Pulmonary hypertension (PH) is an uncommon and poorly described disease in cats. This is the first report of irreversible PH in a kitten with troglostrongylosis. Spot on containing imidacloprid 10%/moxidectin 1% was effective against T. brevior . Troglostrongylus brevior had high pathogenic potential in young patients.